2023
DOI: 10.1002/acn3.51872
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor and binding protein genes variants in patients with migraine

Elena García‐Martín,
Santiago Navarro‐Muñoz,
Pedro Ayuso
et al.

Abstract: Background/ObjectivesSeveral studies have shown a relationship between vitamin D and migraine, including the association between decreased serum 25‐hydroxyvitamin D in patients with migraine and the positive effects of vitamin D supplementations in the therapy of this disease. Two single‐nucleotide variants (SNVs) vitamin D receptor (VDR) gene, VDR rs2228570, and VDR rs731236 have shown an association with migraine risk in a previous case–control association study, while an exome sequencing study identified a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(114 reference statements)
0
0
0
Order By: Relevance
“… 100 However, a study that genotyped 290 patients diagnosed with migraine and 300 matched controls suggested no association between the polymorphisms of VDBP single nucleotide polymorphisms and the risk of developing migraine. 101 Similarly, another cross-sectional prospective study with 52 patients with migraine and 49 controls found that serum VDBP levels did not correlate with migraine or headache characteristics, including aura, attack severity/frequency/duration, and disease duration. 102 Given the current state of research, evidence is scarce to establish a direct relationship between VDBP and migraine.…”
Section: Clinical Implications Of Vdbp In Neurological Disordermentioning
confidence: 95%
“… 100 However, a study that genotyped 290 patients diagnosed with migraine and 300 matched controls suggested no association between the polymorphisms of VDBP single nucleotide polymorphisms and the risk of developing migraine. 101 Similarly, another cross-sectional prospective study with 52 patients with migraine and 49 controls found that serum VDBP levels did not correlate with migraine or headache characteristics, including aura, attack severity/frequency/duration, and disease duration. 102 Given the current state of research, evidence is scarce to establish a direct relationship between VDBP and migraine.…”
Section: Clinical Implications Of Vdbp In Neurological Disordermentioning
confidence: 95%